Psychiatric Comorbidities and Liver Injury Are Associated With Unbalanced Plasma Bile Acid Profile During Methamphetamine Withdrawal - Ma, Yuru; Wu, Hongjin; Wang, Huawei; Chen, Fengrong; Xie, Zhenrong; Zhang, Zunyue; Peng, Qingyan; Yang, Jiqing; Zhou, Yong; Chen, Cheng; Chen, Minghui; Zhang, Yongjin; et al. (Frontiers in Endocrinology, 2022)
Background: The pathogenesis of methamphetamine use disorders (MUDs) remains largely unknown; however, bile acids may play a role as potential mediators of liver injury and psychiatric comorbidities. The aim of this study was to characterize bile acid (BA) profiles in plasma of patients with MUDs undergoing withdrawal. Methods: Liver functions and psychiatric symptoms were evaluated in a retrospective cohort (30 MUDs versus 30 control subjects) and an exploratory cohort (30 MUDs including 10 subjects each at the 7-day, 3-month, and 12-month withdrawal stages versus 10 control subjects). BA compositions in plasma samples from MUD patients in the exploratory cohort were determined by gas-liquid chromatography. Results: Both psychiatric comorbidities and methamphetamine-induced liver injury were observed in patients in both MUD cohorts. The plasma concentrations of the total BA, cholic acid (CA), and chenodeoxycholic acid (CDCA) were lower in MUD patients relative to controls. The maximum decline was observed at the 3-month stage, with gradual recovery at the 12-month stage. Notably, the ratios of deoxycholic acid (DCA)/CA and lithocholic acid (LCA)/CDCA were statistically significant at the 3-month stage comparing with controls. Significant correlations were found between the LCA/CDCA and taurolithocholic acid (TLCA)/CDCA ratios and the levels of alanine transaminase and aspartate aminotransferase, and between the LCA/CDCA ratio and the HAM-A score. Conclusion: BA profile during METH withdrawal were markedly altered, with these unbalanced BAs being associated with liver injury. The associations between BA profiles and psychiatric symptoms suggest an association between specific BAs and disease progression, possibly through the liver-brain axis.